The reader - Chee, Traci (2016)
"Set in a world where reading is unheard-of, Sefia makes use of a mysterious object to track down who kidnapped her aunt Nin and what really happened the night her father was murdered"--
Keywords: Books and reading -- Fiction; Robbers and outlaws -- Fiction; Adventure and adventurers -- Fiction; Kidnapping -- Fiction; Murder -- Fiction; Orphans -- Fiction; Fantasy; Books and reading -- Juvenile fiction; Kidnapping -- Juvenile fiction; Murder -- Juvenile fiction; Orphans -- Juvenile fiction